Experimental Research on Impinging Slot Jet on a Concave Surface - Effects of Impinging Height and Reynolds Number - Hoang, Thi Kim Dung (Old Journal, 2017)
Experimental research of single slot impinging jet upon a concave surface were conducted by classical Particle Image Velocimetry (PIV) and infrared thermography. Main parameters of this research were nozzle exit Reynolds number (Re_b=1400-6400), dimensionless impinging height (H/b=3-7), relative curvature of wall (D_c/b=5) and little dissymmetric outlet flow (e/b=0.8). Results indicated that impinging jet oscillated at three semi-stable different point at high impinging height while it stabilized at a position at small impinging height. Therefore, oscillation of impinging jet generated a uniform heat transfer at high impinging height while stabilized impinging jet caused an asymmetric heat transfer at low impinging height.